Hepato-protective Potentials of methanol leaf extract and chromatographic fractions of Solanum aethiopicum on Cyclophosphamide-induced Megaloblastic Anaemia in Rats - AJA, OTI AGHA; OKAFOR, POLYCARP N.; EGBACHUKWU, SIMEON I. (Sahel Journal of Life Sciences FUDMA, 2024)
The hepato-protective potentials of methanol leaf extract and chromatographic fractions of Solanum aethiopicum on cyclophosphamide-induced megaloblastic anaemia in rats were evaluated using standard protocols. The extracts toxicity study, proximate, vitamins and phytochemical analyses were investigated. The fractionation and thin-layer chromatography yielded five fractions. Proximate constituents results include moisture (39.46±0.08%), dry matter (60.54±0.08), ash content (72.12±0.02%), crude fibre (11.97±0.04%), crude fat (2.56±0.02%), protein content (15.48±0.07%); Important vitamins such as Vit. C (53.27±0.05mg/kg), Vit. B9 (60.24±0.50mg/kg), and Vit. B12 (63.98±0.01mg/kg); and phytochemicals such as alkaloids (5.23±0.02mg/100g), flavonoids (21.49±0.16mg/100g), phenols (25.82±0.26mg/100g), and tannins (3.09±0.04mg/100g), were observed in the sample. The results revealed a significant (P < 0.05) increase in total protein, albumin, and globulin concentrations in all the groups treated with various doses of S. aethiopicum leaf extract when compared with group II rats. ALT, AST, ALP and total bilirubin levels significantly (P < 0.05) decreased in all the groups treated with various doses of S. aethiopicum leaf extract when compared with group II rats. The result further revealed a significant (P < 0.05) decrease in ALT, AST, ALP and Total bilirubin concentrations across all the groups treated with the five fractions in comparison with group II rats. The observed bioactive constituents of S. aethiopicum leaf could be behind the different degrees of efficacy exhibited by the fractions and crude extracts in this study. Therefore, S. aethiopicum leaf has beneficial hepato-protective properties in rats at a therapeutic dose that supports its use in the treatment of hepatic diseases.